ANALISIS IMPLEMENTASI AUDIT PERBANKAN SYARIAH DI INDONESIA - Puja Lestari; Dewi Susilowati; Wahyudin Wahyudin (SAR (Soedirman Accounting Review) : Journal of Accounting and Business, 2020)
This study aims to analyze the suitability of audit practices in Islamic Banking with existing auditing standards in Indonesia. The unit of analysis in this study is the state-owned Sharia Commercial Bank, namely PT. Bank Syariah Mandiri and privately owned, namely PT. Bank Muamalat Indonesia Tbk. This research uses qualitative methods, using case studies. Data collection was obtained by conducting interviews and analyzing annual reports from 2015 to 2017. The results showed that the audit framework, audit scope, audit quality, audit charter, audit process, and reporting requirements conform to appropriate auditing standards in Indonesia. This study found facts related to sharia auditing in terms of qualified human resources in terms of knowledge of sharia auditing and principles.